A Poly-γ-Glutamic Acid/ε-Polylysine Hydrogel: Synthesis, Characterization, and Its Role in Accelerated Wound Healing - Jiaqi Li; Yuanli Huang; Yalu Wang; Qianqian Han (Gels)
Wound healing is a complex biological process involving inflammation, proliferation, and remodeling phases. Effective healing is essential for maintaining skin integrity, driving the need for advanced materials like hydrogels, known for their high water retention and tunable mechanical properties. In this study, we synthesized a biocompatible composite hydrogel composed of γ-polyglutamic acid (γ-PGA) and ε-polylysine (ε-PL) through a Schiff base reaction, forming a stable crosslinked network. Its physicochemical properties, including rheological behavior and swelling capacity, were systematically evaluated. Biocompatibility was assessed via in vitro hemolysis and cytotoxicity assays, and in vivo testing was performed using a full-thickness skin defect model in Sprague Dawley (SD) rats to evaluate wound-healing efficacy. The PGA-PL hydrogel demonstrated excellent physicochemical properties, with a maximum swelling ratio of 65.6%, and biocompatibility as evidenced by low hemolysis rates (<5%) and high cell viability (>80%). It promoted wound healing by inhibiting the inflammatory response, reducing levels of the inflammatory cytokine IL-6, enhancing angiogenesis, and accelerating collagen deposition. The hydrogel showed complete biodegradation within 21 days in vivo without inducing a significant inflammatory response and significantly accelerated wound healing, achieving an 86% healing rate within 7 days compared to 67% in the control group. The PGA-PL composite hydrogel exhibits excellent mechanical strength and biocompatibility, and its effective wound-healing capabilities lay the groundwork for future development and optimization in various tissue engineering applications.